Model OLD0: A Physical Parameterization for Clear-Sky Downward Longwave Radiation - Juan Carlos Ceballos; Diego Pereira Enoré; Jaidete Monteiro de Souza; Francisco Luiz Leitão de Mesquita (Revista Brasileira de Meteorologia)
Abstract Downward longwave irradiance DLF is one of the main components of the surface radiation balance (SRB), but its direct measurement is currently limited. Clouds modulate its behavior, and clear-sky DLF0 is predominant in composition of the final DLF value. It is shown that in mid-latitude and tropical atmospheres, DLF0 can be represented as the sum of fluxes from three distinct spectral regions: R1 (λ < 7.5 µm), R2 (7.5 to 14 µm), and R3 (λ > 14 µm). R1 and R3 are closely described by blackbody radiation at screen temperature (Tscr), while R2 exhibits a mean emissivity that primarily depends on total precipitable water (w). It is presented a simple yet consistent physically-based model (hereafter denoted by OLD0), suitable for estimation of DLF0 at ground level. Validation of OLD0 with ground-based data of a worldwide set of 21 stations shows fair accuracy with bias MBE lower than 6 W.m-2 and spread (standard deviation STD) lower than 12 W.m-2 for typical values DLF0 ~ 300-400 W.m-2, compatible with surface pyrgeometer measures. The proposed algorithm outperforms existing methods, achieving a mean bias error (in module |MBE|) of approximately 2.8 W.m-2. In contrast, other widely used algorithms typically exhibit |MBEs| ranging from 8.1 to 15.9 W.m-2.